Comparing Strategies Targeting Osteoporosis to Prevent Fractures After an Upper Extremity Fracture (C‐STOP Trial): A Randomized Controlled Trial. (22nd August 2018) - Majumdar, Sumit R; McAlister, Finlay A; Johnson, Jeffrey A; Rowe, Brian H; Bellerose, Debbie; Hassan, Imran; Lier, Douglas A; Li, Stephanie; Maksymowych, Walter P; Menon, Matthew; Russell, Anthony S; Wirzba, Brian; et al.
ABSTRACT: We compared osteoporosis care after upper extremity fragility fracture using a low‐intensity Fracture Liaison Service (FLS) versus a high‐intensity FLS in a pragmatic patient‐level parallel‐arm comparative effectiveness trial undertaken at a Canadian academic hospital. A low‐intensity FLS (active‐control) that identified patients and notified primary care providers was compared to a high‐intensity FLS (case manager) where a specially‐trained nurse identified patients, investigated bone health, and initiated appropriate treatment. A total of 361 community‐dwelling participants 50 years or older with upper extremity fractures who were not on bisphosphonate treatment were included; 350 (97%) participants completed 6‐month follow‐up undertaken by assessors blinded to group allocation. The primary outcome was difference in bisphosphonate treatment between groups 6 months postfracture; secondary outcomes included differences in bone mineral density (BMD) testing and a predefined composite measure termed "appropriate care" (taking or making an informed decision to decline medication for those with low BMD; not taking bisphosphonate treatment for those with normal BMD). Absolute differences (%), relative risks (RR with 95% confidence intervals [CIs]), number‐needed‐to‐treat (NNT), and direct costs were compared. A total of 181 participants were randomized to active‐control and 180 to case‐manager using computer‐generated randomization; the groups were similar on study entry. At 6 months, 51 (28%) active‐control versus 86 (48%) case‐manager participants started bisphosphonate treatment (20% absolute difference; RR 1.70; 95% CI, 1.28 to 2.24; p < 0.0001; NNT = 5). Of active‐controls, 108 (62%) underwent BMD testing compared to 128 (73%) case‐managed patients (11% absolute difference; RR 1.17; 95% CI, 1.01 to 1.36; p = 0.03). Appropriate care was received by 76 (44%) active‐controls and 133 (76%) case‐managed participants (32% absolute difference; RR 1.73; 95% CI, 1.43 to 2.09; p < 0.0001). The direct cost per participant was 18 Canadian (CDN) for the active‐control intervention compared to 66 CDN for the case‐manager intervention. In summary, case‐management led to substantially greater improvements in bisphosphonate treatment and appropriate care within 6 months of fracture than the active control. © 2018 American Society for Bone and Mineral Research.